Innovation of Educational Curriculum in Salafiyah Islamic Boarding Schools - Abidin, Achmad Anwar; Sulaiman, Muhammad (Jurnal Kependidikan Islam, 2024)
This article is presented to describe the innovation of developing Islamic education curriculum at Riyadlul Mubtadiin Islamic Boarding School. which includes: development of learning approaches, learning systems, learning methods, the process of involving educational stakeholders. The method used in this study is a qualitative method, with a historical-instructionalist approach, with an approach able to see every side of development in the perspective of the History of Islamic learning. The result of this paper is the modernization of Islamic education at the Riyadlul Mubtadiin Islamic Boarding School including the development of a learning curriculum from pure salaf to semi-salaf. The learning methods taught are very varied, different from before. There is an evaluation of the program carried out both quarterly and every six months. Evalausion includes: Spective, Cognitive and Psychomotor. As well as the involvement of stakeholders, especially alumni, in determining the policy direction of institutional development.